PENGARUH BIMBINGAN KELOMPOK DENGAN TEKNIK PROBLEM SOLVING UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS VIII SMP N 2 TEGOWANU - Fanny Mawardani Putri; Heri Septadi Ismanto; Agus Setiawan (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
Fanny Mawardani Putri. NPM 19110206. "The Effect of Group Tutoring Using Problem Solving Techniques to Improve Learning Outcomes for Class VIII Students at SMP Negeri 2 Tegowanu" Thesis. Guidance and Counseling Study Program. Faculty of Science Education. PGRI UNIVERSITY Semarang. Supervisor I: Dr. Heri Septadi Ismanto, S.Pd., M.Pd., Kons. Supervisor II: Agus Setiawan S.Pd., M.Pd. 2024. Education is the most important thing in human life, meaning that every Indonesian has the right to get it and is expected to always develop in it. The aim of this research is to determine the effect of group guidance using problem solving techniques to improve the learning outcomes of class VIII students at SMP Negeri 2 Tegowanu. The research used in this research is quantitative with experimental methods. This research uses a pretest-posttest control group design. Based on the pretest results in the control class and experimental class regarding the scale of learning outcomes, it can be seen that in the experimental class there were 10 students in the low category with a percentage of 100%. Meanwhile in the control class there were 10 students in the low category with a percentage of 100%. Based on the results of the experimental class and control class posttest above. In the experimental class, the highest score was 55 and the lowest score was 46, while in the control class the highest score was 46 and the lowest score was 38. Based on the results of the difference test calculation between the two data averages presented in the table above, it is known that the Levene's test for equality of variance column has significant value of 0.63 (p> 0.05). Based on the results of the analysis, it can be concluded that there is an influence of group guidance with problem solving techniques to improve the learning outcomes of class VIII students at SMP Negeri 2 Tegowanu. From the results of the analysis, it was found that the average value of the experimental class before the group guidance service using problem solving techniques was carried out was 37.8 and after the group guidance service using problem solving techniques was carried out it increased, namely 48.7. Based on the results of the research that has been carried out, the researchers put forward several suggestions, namely: Group guidance services using problem solving techniques are very beneficial for students at school. So it is hoped that the school can implement service delivery using problem solving techniques. Guidance Counseling Teachers can develop new innovations using this problem solving technique. Students who have participated in group guidance services using problem solving techniques are expected to be able to maintain the commitments they have made and be able to actualize themselves better. Guidance and counseling teachers should try and apply it in group guidance services with problem solving techniques as one of the techniques that can make students more active, creative and fun. Future researchers might be able to take a wider sample and varying levels of education, as well as look for other factors possessed by students. Fanny Mawardani Putri. NPM 19110206. "The Effect of Group Tutoring Using Problem Solving Techniques to Improve Learning Outcomes for Class VIII Students at SMP Negeri 2 Tegowanu" Thesis. Guidance and Counseling Study Program. Faculty of Science Education. PGRI UNIVERSITY Semarang. Supervisor I: Dr. Heri Septadi Ismanto, S.Pd., M.Pd., Kons. Supervisor II: Agus Setiawan S.Pd., M.Pd. 2024.Education is the most important thing in human life, meaning that every Indonesian has the right to get it and is expected to always develop in it. The aim of this research is to determine the effect of group guidance using problem solving techniques to improve the learning outcomes of class VIII students at SMP Negeri 2 Tegowanu. The research used in this research is quantitative with experimental methods. This research uses a pretest-posttest control group design. Based on the pretest results in the control class and experimental class regarding the scale of learning outcomes, it can be seen that in the experimental class there were 10 students in the low category with a percentage of 100%. Meanwhile in the control class there were 10 students in the low category with a percentage of 100%.Based on the results of the experimental class and control class posttest above. In the experimental class, the highest score was 55 and the lowest score was 46, while in the control class the highest score was 46 and the lowest score was 38. Based on the results of the difference test calculation between the two data averages presented in the table above, it is known that the Levene's test for equality of variance column has significant value of 0.63 (p> 0.05). Based on the results of the analysis, it can be concluded that there is an influence of group guidance with problem solving techniques to improve the learning outcomes of class VIII students at SMP Negeri 2 Tegowanu.From the results of the analysis, it was found that the average value of the experimental class before the group guidance service using problem solving techniques was carried out was 37.8 and after the group guidance service using problem solving techniques was carried out it increased, namely 48.7. Based on the results of the research that has been carried out, the researchers put forward several suggestions, namely: Group guidance services using problem solving techniques are very beneficial for students at school. So it is hoped that the school can implement service delivery using problem solving techniques. Guidance Counseling Teachers can develop new innovations using this problem solving technique. Students who have participated in group guidance services using problem solving techniques are expected to be able to maintain the commitments they have made and be able to actualize themselves better. Guidance and counseling teachers should try and apply it in group guidance services with problem solving techniques as one of the techniques that can make students more active, creative and fun. Future researchers might be able to take a wider sample and varying levels of education, as well as look for other factors possessed by students.